2003
DOI: 10.1021/bp034032c
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Selection of Hyperthermophilic Esterases for Resolution of 2‐Arylpropionic Esters

Abstract: Homologues to Carboxylesterase NP and Candida rugosa lipase, used for the chiral separation of racemic mixtures of 2-arylpropionic methyl esters, were identified by BLAST searches of available genome sequences for hyperthermophilic microorganisms. Two potential candidates were identified: a putative lysophospholipase from Pyrococcus furiosus (Pfu-LPL) and a carboxylesterase from Sulfolobus solfataricus P1 (Sso-EST1). Although both enzymes showed hydrolytic preference toward the (S) methyl ester, only Sso-EST1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The carboxylesterase from S. solfataricus P1 (Sso Est1) showed a specific reaction toward the Snaproxen ester in co-solvent reaction conditions. 25) But Est3 displayed a different catalytic pattern toward anarylpropionic methylester substrate, ketoprofen methylester, containing the same chiral center. The selectivity toward substrates observed in previous literature might be elucidated by the fact that the change in the sidechain structure of the substrate leads to a drastic change in reaction rate and enantioselectivity.…”
Section: Discussionmentioning
confidence: 97%
“…The carboxylesterase from S. solfataricus P1 (Sso Est1) showed a specific reaction toward the Snaproxen ester in co-solvent reaction conditions. 25) But Est3 displayed a different catalytic pattern toward anarylpropionic methylester substrate, ketoprofen methylester, containing the same chiral center. The selectivity toward substrates observed in previous literature might be elucidated by the fact that the change in the sidechain structure of the substrate leads to a drastic change in reaction rate and enantioselectivity.…”
Section: Discussionmentioning
confidence: 97%
“…The enzyme hydrolyzed the ( R )-ester of racemic ketoprofen methylester and showed an enantiomeric excess of 80% with a conversion rate of 20% in 32 h. In another study, the esterase Sso-Est1 from S. solfataricus P1 (Sehgal et al 2001 ) was identified as homolog to the mesophilic Bacillus subtilis ThaiI-8 esterase (CNP) (Quax and Broekhuizen 1994 ) and Candida rugosa lipase (CRL) (Lee et al 2001 ), which are used for the chiral separation of racemic mixtures of 2-arylpropionic methyl esters. The enzyme was characterized biochemically for its ability to resolve mixtures of ( R,S )-naproxen methyl ester under a variety of reaction environments (Sehgal and Kelly 2002 , 2003 ). Sso-Est1 showed a specific reaction toward the ( S )-naproxen ester in co-solvent reaction conditions with an enantiomeric excess of ≥90%.…”
Section: Properties Of Characterized Esterasesmentioning
confidence: 99%
“…β -mannanases are widely applied in pulp and paper processing [4], feed [5], food [6], pharmaceutical [7], oil, and textile industries [8] to randomly hydrolyze the β -1,4 mannopyranoside linkage in mannan, galactomannan, glucomannan, and galactoglucomannan.…”
Section: Introductionmentioning
confidence: 99%